2012
DOI: 10.1037/a0027791
|View full text |Cite
|
Sign up to set email alerts
|

Models of verbal working memory capacity: What does it take to make them work?

Abstract: Theories of working memory (WM) capacity limits will be more useful when we know what aspects of performance are governed by the limits and what aspects are governed by other memory mechanisms. Whereas considerable progress has been made on models of WM capacity limits for visual arrays of separate objects, less progress has been made in understanding verbal materials, especially when words are mentally combined to form multi-word units or chunks. Toward a more comprehensive theory of capacity limits, we exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
126
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 125 publications
(157 citation statements)
references
References 114 publications
(225 reference statements)
18
126
1
1
Order By: Relevance
“…The mean spans for spatial locations in the two experiments with the spatial fit task and the parity task during retention interval were very close to each other (3.12 and 3.21, respectively) but lower than for letters. The small advantage in span for letters compared with spatial locations could result from the supplementary involvement of some longterm memory component, as suggested by Cowan, Rouder, Blume, and Saults (2012). Still, these values are very much in line with the work of Cowan (2001) demonstrating a limit at about three to four items in WM.…”
Section: Discussion: Experiments 1-3supporting
confidence: 83%
“…The mean spans for spatial locations in the two experiments with the spatial fit task and the parity task during retention interval were very close to each other (3.12 and 3.21, respectively) but lower than for letters. The small advantage in span for letters compared with spatial locations could result from the supplementary involvement of some longterm memory component, as suggested by Cowan, Rouder, Blume, and Saults (2012). Still, these values are very much in line with the work of Cowan (2001) demonstrating a limit at about three to four items in WM.…”
Section: Discussion: Experiments 1-3supporting
confidence: 83%
“…According to this principle, it is very reasonable to accept that fewer objects than single features can be maintained. Our results concerning memory for cross-domain associations were more in line with Allen et al (2006) and Cowan et al (2012) for within-domain combinations and revealed a lower capacity for objects than single features. Cowan et al's idea of chunk decomposition could explain the results obtained in the present study and as such apply to the maintenance capacity limit of the episodic buffer.…”
Section: Discussionsupporting
confidence: 71%
“…About three "chunks" could be maintained, while these chunks were often incomplete. Cowan et al (2012) described this phenomenon as chunk decomposition. Chunks can fall apart in their different components and in that case occupy more than one slot within WM.…”
Section: Discussionmentioning
confidence: 99%
“…Work along this line needs to flesh out in more detail how the resource limit is to be combined with the mechanisms of interference. (Baddeley et al, 1975;Schweickert & Boruff, 1986) Neo-Piagetian general resource model (Case et al, 1982) Feature model (Nairne, 1990) Limited-capacity trace-decay theory (Jensen, 1988;Salthouse, 1996) Multiple-resource model (Alloway et al, 2006;Logie, 2011) Interference model (Oberauer & Kliegl, 2001 Primacy model (Page & Norris, 1998) 3CAPS (Just & Carpenter, 1992) SOB (Lewandowsky & Farrell, 2008b) and SOB-CS (Oberauer, Lewandowsky, et al, 2012) Task-switching model (Towse & Hitch, 1995;Towse, Hitch, & Hutton, 2000) Slot model (Luck & Vogel, 2013;Cowan et al, 2012) Temporal-clustering-andsequencing model (Farrell, 2012) Computational phonological loop model (Burgess & Hitch, 1999 Resource models of visual WM Time-based resource-sharing model Camos et al, 2009) Note: Theories in the table were selected because they attribute the WM capacity limit unambiguously to decay, limited resources, or interference, respectively. Some theories of WM were not included because they combine two or three of the hypotheses, or make no clear assumptions about what causes the capacity limit.…”
Section: Resultsmentioning
confidence: 99%
“…(2) Alternatively, WM capacity has been characterized as a limited resource that needs to be shared by representations held available simultaneously and processes to be carried out at the same time (Case, Kurland, & Goldberg, 1982;Just & Carpenter, 1992;Ma, Husain, & Bays, 2014). This resource could be continuous or discrete, and the discrete variant is often referred to as a "slot model" (Cowan, Rouder, Blume, & Saults, 2012). (3) A third approach is to explain the limited capacity of WM WM Capacity 4 as arising from interference between representations that do not decay on their own and are not resource-limited (Nairne, 1990;Oberauer & Kliegl, 2006;Saito & Miyake, 2004).…”
Section: Introductionmentioning
confidence: 99%